Transfer and Enzyme-Mediated Metabolism of Oxidized Phosphatidylcholine and Lysophosphatidylcholine between Low- and High-Density Lipoproteins - Naoko Sawada; Takashi Obama; Mirei Mizuno; Kiyoshi Fukuhara; Sanju Iwamoto; Toshihiro Aiuchi; Tomohiko Makiyama; Hiroyuki Itabe (Antioxidants, 2020)
Oxidized low-density lipoprotein (oxLDL) and oxidized high-density lipoprotein (oxHDL), known as risk factors for cardiovascular disease, have been observed in plasma and atheromatous plaques. In a previous study, the content of oxidized phosphatidylcholine (oxPC) and lysophosphatidylcholine (lysoPC) species stayed constant in isolated in vivo oxLDL but increased in copper-induced oxLDL in vitro. In this study, we prepared synthetic deuterium-labeled 1-palmitoyl lysoPC and palmitoyl-glutaroyl PC (PGPC), a short chain-oxPC to elucidate the metabolic fate of oxPC and lysoPC in oxLDL in the presence of HDL. When LDL preloaded with d13-lysoPC was mixed with HDL, d13-lysoPC was recovered in both the LDL and HDL fractions equally. d13-LysoPC decreased by 50% after 4 h of incubation, while d13-PC increased in both fractions. Diacyl-PC production was abolished by an inhibitor of lecithin-cholesterol acyltransferase (LCAT). When d13-PGPC-preloaded LDL was incubated with HDL, d13-PGPC was transferred to HDL in a dose-dependent manner when both LCAT and lipoprotein-associated phospholipase A2 (Lp-PLA2) were inhibited. Lp-PLA2 in both HDL and LDL was responsible for the hydrolysis of d13-PGPC. These results suggest that short chain-oxPC and lysoPC can transfer between lipoproteins quickly and can be enzymatically converted from oxPC to lysoPC and from lysoPC to diacyl-PC in the presence of HDL.